2009
DOI: 10.1007/s11771-009-0076-5
|View full text |Cite
|
Sign up to set email alerts
|

Stability and nonlinear dynamic behavior of drilling shaft system in copper stave deep hole drilling

Abstract: The stability and nonlinear dynamic behavior of drilling shaft system in copper stave deep hole drilling were analyzed. The effects of the fluctuation of the cutting force, the mass eccentricity and the hydrodynamic forces of cutting fluid could be taken into consideration in the model of drilling shaft system. Based on the isoparametric finite element method, the variational form of Reynolds equation in hydrodynamic fluid was used to calculate nonlinear hydrodynamic forces and their Jacobian matrices simultan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…In addition, it can be seen from Figures 7-9 that with an increase in rotational speed, whirling magnitude value at nodal point increases obviously, whereby resulting in an increase in roundness errors of the holes to be machined. As a result, this law has been proved in the correlative experiment [7,10]. "D" region is the complete unstable machining region for the drilling shaft.…”
Section: Analysis Of Numerical Examplesmentioning
confidence: 74%
See 3 more Smart Citations
“…In addition, it can be seen from Figures 7-9 that with an increase in rotational speed, whirling magnitude value at nodal point increases obviously, whereby resulting in an increase in roundness errors of the holes to be machined. As a result, this law has been proved in the correlative experiment [7,10]. "D" region is the complete unstable machining region for the drilling shaft.…”
Section: Analysis Of Numerical Examplesmentioning
confidence: 74%
“…To ensure the scheme accuracy, the drilling shaft system in this paper is modeled on the basis of [7], where the nonlinear vibration behaviors of drilling shaft was investigated when considering the imbalance forces of drilling shaft, cutting forces fluctuation, and nonlinear cutting fluid forces, and the numerical results was confirmed by the experiments. So, the deep-hole drilling shaft system model with the multiauxiliary supports is established as shown in Figure 1.…”
Section: Mathematical Modeling Of Drilling Shaft Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Drilling shaft system as a rotating machine is a typical nonlinear dynamic system, and hence nonlinear hydrodynamic forces of cutting fluid do not have analytical formulation in fact. Kong et al [10] established the concentration mass dynamic model of drilling shaft system with the multi-degrees but without considering the effects of inertia and shear, and proposed a method to calculate the nonlinear hydrodynamic forces of cutting fluids and their Jacobian matrices of compatible accuracy simultaneously, and in addition, it was found that the mass eccentricity can inhibit the whirling motion of drilling shaft reported from the experimental results. Hussien et al [11] studied dynamic drilling shaft modeling with one-span and developed a mathematical approach to study the whirling motion of a continuous boring bar-workpiece system by transforming the problem into nonhomogeneous equations with homogenous boundary conditions.…”
Section: Introductionmentioning
confidence: 99%